A STUDY ON ROLE OF BLOCKCHAIN TECHNOLOGY IN BANKING SECTOR (International Journal of Food and Nutritional Sciences, 2022)
A blockchain is an ordered, decentralized and immutable ledger that allows a recording of transactions in a network. Over the recent years, blockchain has emerged to be a technology that can be applied in various sectors. It has promised to be the technology that will allow transactions simply, effectively, safely and cheaply. It is core, underlying technology with promising application prospects in the banking industry. With the increasing need for modernization in our lives, people are open to accepting new technologies. Blockchain technology can be described as data structure that holds transactional records a while ensuring security, transparency and decentralization, the chances of any fraudulent activity or duplication of transactions is eliminated without the need of third-party. Banks are among the most seasoned and great monetary middle people in India. A few huge Changes have happened in the working financial area. Banking in India has seen an extreme change from Regular banking to accommodation banking. The main objective my study is to understand and analyses of effectiveness of blockchain technology in banking sector along with its challenges and data privacy and security of customers in blockchain technology. The primary data has been collected for the study and descriptive research methodology has been used. This study mainly focuses on role of blockchain technology in banking sector.